2020
DOI: 10.1016/j.geobios.2020.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Taphonomic pathway of exceptionally preserved fossils in the Lower Ordovician of Morocco

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 63 publications
4
42
0
1
Order By: Relevance
“…The sedimentary structures found in the Fezouata Shale are typical of a storm-wave dominated environment (Fig. 4A) (Martin et al, 2016;Vaucher et al, 2016Vaucher et al, , 2017Saleh et al, 2020a). These storms were erosive, and their deposits are characterized by the presence of normally graded beds (Fig.…”
Section: Question 2: Surface Processesin-situ Burial By Distal Tempestitesmentioning
confidence: 96%
See 3 more Smart Citations
“…The sedimentary structures found in the Fezouata Shale are typical of a storm-wave dominated environment (Fig. 4A) (Martin et al, 2016;Vaucher et al, 2016Vaucher et al, , 2017Saleh et al, 2020a). These storms were erosive, and their deposits are characterized by the presence of normally graded beds (Fig.…”
Section: Question 2: Surface Processesin-situ Burial By Distal Tempestitesmentioning
confidence: 96%
“…A statistical correlation between sedimentological data from cores and palaeontological data from outcrops showed that exceptional preservation is associated with one of the most distal facies of the Fezouata Shale (Fig. 5) (Saleh et al, 2020a). This facies is characterized with an abundance of mudstones (i.e.…”
Section: Question 2: Surface Processesin-situ Burial By Distal Tempestitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Replacement of fossil tissues by iron oxides often results from the oxidation of pyrite (e.g. [44][45][46]), which forms in large quantities in such organically rich depositional environments, especially considering that sulfate was present (see below). Besides Fe, major-to-trace elemental mapping using SRS-XRF (figure 2, electronic supplementary material, figure S1, S2) shows that the fossil is also enriched in Cu, As (figure 2b,c,e) and to a lesser extent Ca.…”
Section: Preservation and Palaeoenvironmentmentioning
confidence: 99%